1995
DOI: 10.1103/physreve.51.1449
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the response time of GaAs as a photoemitter

Abstract: An experimental investigation was carried out to measure the response time of GaAs in negative electron affinity conditions as a photoemitter. During the experiment, the photocathode was excited by a short-pulse (38 ps rms) frequency-doubled Nd:YLF laser. Results show that the rms response time of GaAs is shorter than 40 ps

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Measurements of bulk 6) and thin film GaAs 7) have shown that the temporal response can be explained by a diffusion model, which assumes a random walk of individual electrons, using two experimentally determined constants; the photoabsorption length À1 and the diffusion coefficient D. Measurements when illuminated by a shorter wavelength of $500 nm have shown a faster response time; 8,9) this is because of its shorter photo absorption length.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of bulk 6) and thin film GaAs 7) have shown that the temporal response can be explained by a diffusion model, which assumes a random walk of individual electrons, using two experimentally determined constants; the photoabsorption length À1 and the diffusion coefficient D. Measurements when illuminated by a shorter wavelength of $500 nm have shown a faster response time; 8,9) this is because of its shorter photo absorption length.…”
Section: Introductionmentioning
confidence: 99%
“…These neglected terms, along with some second order perturbation terms, are linear in k and cause a shift of the valence band maxima from the T point when appropriately accounted for. [21] The spin orbit interaction terms included in the interaction matrix are of the form 12) <Y|(t)|#J 0 |£tU)) = +(-)iA , (2.13) [2][3][4][5][6][7][8][9][10][11][12][13][14] This interaction requires the eigenfunctions to be states of J and rrij. Kane obtained solutions for the complete interaction, Hk.…”
Section: Spin Orbit Interactionmentioning
confidence: 99%
“…[3] [4] With a thin active layer, the average electron escape time is presumably much shorter than any spin relaxation times associated with the material and the effect of spin depolarization within the semiconductor is thus minimized. Secondly, the cathode may be used either in a CW mode or pulsed, with pulse lengths as short as 40 psec, [5] by appropriate choice of pump laser. The spin polarization is promptly reversible by reversing the helicity of the pump laser.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the response time for GaAs photocathodes have been made only with bulk samples [Aleksandrov 1995. Aleksandrov et al, placed an upper limit of 40ps on the response time, whereas Hartmann et al, found it to be about 30ps.…”
Section: Photocathode Response Timementioning
confidence: 99%